2021
DOI: 10.2196/23365
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Synthesis of Digital Interventions to Mitigate the Negative Impact of the COVID-19 Pandemic on Public Mental Health: Rapid Meta-review

Abstract: Background Accumulating evidence suggests the COVID-19 pandemic has negative effects on public mental health. Digital interventions that have been developed and evaluated in recent years may be used to mitigate the negative consequences of the pandemic. However, evidence-based recommendations on the use of existing telemedicine and internet-based (eHealth) and app-based mobile health (mHealth) interventions are lacking. Objective The aim of this study w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
122
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 167 publications
(139 citation statements)
references
References 118 publications
3
122
0
6
Order By: Relevance
“…Information and communication technologies may be particularly important in alleviating COVID-19-related psychosocial consequences [31]. For instance, smartphone applications (apps) help individuals to remotely interact with others (e.g., by using videoconferencing software) and digital interventions, which do not require face-to-face contact (e.g., Internet-based interventions [eHealth] and mobile health applications [mHealth apps]), may help to increase public mental health during health crises [31].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Information and communication technologies may be particularly important in alleviating COVID-19-related psychosocial consequences [31]. For instance, smartphone applications (apps) help individuals to remotely interact with others (e.g., by using videoconferencing software) and digital interventions, which do not require face-to-face contact (e.g., Internet-based interventions [eHealth] and mobile health applications [mHealth apps]), may help to increase public mental health during health crises [31].…”
Section: Introductionmentioning
confidence: 99%
“…Information and communication technologies may be particularly important in alleviating COVID-19-related psychosocial consequences [31]. For instance, smartphone applications (apps) help individuals to remotely interact with others (e.g., by using videoconferencing software) and digital interventions, which do not require face-to-face contact (e.g., Internet-based interventions [eHealth] and mobile health applications [mHealth apps]), may help to increase public mental health during health crises [31]. Previous studies have shown that digital tools available in major app stores, especially mHealth apps, are already frequently being used, although most developers do not provide information on their evidence base, safety, and effectiveness [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…B. Datensicherheit, Interoperabilität) und gesetzliche Rahmenbedingungen wie das Medizinproduktgesetz erklärt werden. Vereinzelt werden jedoch telemedizinische Ansätze wie Videokonferenzsoftware bereits genutzt, um die Kommunikation zwischen klinischem Personal und Patient*innen zu unterstützen -wie sich nicht zuletzt seit Ausbruch der COVID-19-Pandemie eindrucksvoll gezeigt hat [28]. Gesundheits-und Medizin-Apps kommen hingegen noch nicht zur routinemäßigen Anwendung.…”
Section: Diskussionunclassified